Beyond globalization monetary tools towards a sustainable regional development - Brunnhuber Stefan (2005)
Six global megatrends are considered which are likely to impact any region in the world at any time. Regional solutions to such challenges will require to revisit the currently prevailing assumptions concerning our industrialage money-ystem. Itreveals itself not a neutral component at the service of the system, but instead significantly affects the options available in the real economic sector. Apart from the conventional solutions (neo-liberal and neo-k ynesian approach), complementary monetary solutions arise, which can balance out the whole financial system on a regional level and can lead to a more sustainable and just future.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok